Vodni viri Slovenije - Plut, Dušan (Geografski obzornik, 2003)
The geographic heterogeneity of Slovenia determines different water resources with characteristic seasonal variability as well. The average specific outflow is 3-times, the amount of river water per inhabitant is on the other side 3,7-times above European average. Due to partial purification of wastewaters, the water resources are by deafault overburdened, i.e. especially evident with watercourses. Carst springs and ground water are essential for drinking water supplies. Drought of the year 2003 indicates therefore again the necessity of reasonable water managment in the regions "rich" in the field of water resources.
Keywords: hidrogeografija; vodni viri; vodna bilanca; oskrba z vodo; ecology; ekologija; ekološko ravnotežje; varstvo voda; Slovenia; Slovenija